Feminist theory reader : local and global perspectives - McCann, Carole R.; Kim, Seung-Kyung (Routledge, 2010)
Feminist Theory Reader, second edition, continues its unique approach of anthologizing the important works of feminist theory within a multiracial transnational framework. Classic works in feminist theory by scholars such as Simone De Beauvoir, Gloria Anzaldua, Judith Butler, belle hooks, Nancy Hartsock, Deniz Kandiyoti,and Chandra Talpade Mohanty appear alongside cutting-edge scholarship by Paula Moya, Aiwha Ong, Raewyn Connell, Suzanne Walters, Mrinalina Sinha, and Rhacel Parrenas. The new edition significantly updates both the local and global perspectives that distinguished the first edition, incorporating themes and debates on the rise in the contemporary feminist scholarship.